OPTIMALISASI PERAN PERPUSTAKAAN SEBAGAI SARANA KOMUNIKASI ILMIAH: STUDI KASUS DI PERPUSTAKAAN UNIVERSITAS SEBELAS MARET SURAKARTA - Anawati, Sri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
The college library means of scientific communication must utilize information technology as a means of supporting information dissemination. The library as one of the media in the chain of scientific communication, serves as a center of information both in printed and electronic forms. The research method used is observation of the role of the UNS Library as a means of scientific communication. The role of the UNS Library as a means of scientific communication namely: (1) providing ejournal content, digital library, institutional repository, journals and other publications that is published by UNS; and (2) information literacy, like as user education, collaboration between librarians and lecturers; information retrieval services, and periodical training.